Pluralidade familiar constante na Constituição de 1988: realidade na zona rural de Montes Claros-MG? - Cyntia Mirella Cangussu Fernandes Sales (2019)
The transformations in the way people organize themselves as family members in Brazil have gained prominence in society and in the legal perception about the new types of family arrangements established in the country. These transformations are driven by changes in sociocultural behavior that shape values and interfere in the relationship between people. Although marriage appears as the hegemonic model in the way that families are structured in Brazil, since the 1988 Constitution the non-formal union of persons signed in the affection has been recognized as a family entity, which has promoted the possibility of legal recognition for the numerous family arrangements, previously set aside by Brazilian legislation. But is the plural perspective of families also found in rural areas, especially in the traditional way of life established in family agriculture? This question has been little investigated in Brazil. In this context, the present study aims to identify the existing family arrangements in the Pentáurea Region, in the Santa Rita Rural community, belonging to the municipality of Montes Claros, and to verify if there is conformation with the family plurality praised by the 1988 Brazilian Constitution. As the inclusion of new arrangements in the legally legitimized role gives access to rights already guaranteed to family entities, another question is to verify to what extent this legal system is known to the rural population. The research was anchored in a qualitative approach and counted on the application of semi-structured interviews to a sample of 30 residents in the community of Santa Rita Rural. The results evidenced the existence of a plurality of family entities in the researched rural area, but with the predominance of the traditional married family. Although the Santa Rita Rural community preserves a traditional way of life and has in marriage the main form of constitution of the families established there, there remains identified the plurality of family arrangements represented by the families constituted by the stable union, reconstituted families and single parents, recognized by the Brazilian Constitution of 1988 as family entities worthy of state protection. It was also evident that the proximity to the municipal seat did not change the residents' perception of the rights they have when organizing themselves as a family. Marriage families understand that they have personal and patrimonial rights, but those who live in a stable union do not have the same perception as subjects of rights. There is also evidence that the concept of family in the community is peculiar. Although residents have a sense of the family nucleus to which they belong and the way in which they are structured, the consideration of the family is broader than the mere relation of blood or the relationship that it maintains with spouses or companions. The people interviewed consider the neighbors as members of their own family nucleus, in order to configure a single large extended family in the community.